2015
DOI: 10.1007/s00167-015-3875-2
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant intra-articular glenohumeral injuries in displaced fractures of the lateral clavicle

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
2
6
0
3
Order By: Relevance
“…In our patient population we evaluated and addressed 37.5% of accompanying pathologies. This is comparable to a study conducted by Beirer et al, who performed a diagnostic arthroscopy in every fracture of the lateral clavicle included in their study [14]. Accompanying pathologies were found in 46.4% of cases [14].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our patient population we evaluated and addressed 37.5% of accompanying pathologies. This is comparable to a study conducted by Beirer et al, who performed a diagnostic arthroscopy in every fracture of the lateral clavicle included in their study [14]. Accompanying pathologies were found in 46.4% of cases [14].…”
Section: Discussionsupporting
confidence: 87%
“…This is comparable to a study conducted by Beirer et al, who performed a diagnostic arthroscopy in every fracture of the lateral clavicle included in their study [14]. Accompanying pathologies were found in 46.4% of cases [14]. In 28.6% of these cases the accompanying pathologies were diagnosed and treated accordingly.…”
Section: Discussionsupporting
confidence: 85%
“…The demonstrated results are in context with the literature. In fact, Beirer et al focused on concomitant intra-articular glenohumeral injuries in displaced Fx of the lateral clavicle [17]. The authors found in 13 of 28 patients, additional intra-articular injuries during arthroscopy, completing the actual open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the fact that scapular Fx are a predictor for a great number of concomitant life-threatening injuries, isolated scapula body Fx have great potential to cause significant pain and to decrease the normal function of the shoulder girdle. Previous research has shown that concomitant intra-articular injuries of the glenohumeral joint in acromioclavicular joint injuries and in lateral clavicula fractures present an incidence of up to 46%, thus should be treated operatively to avoid significant loss of function in the glenohumeral joint [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This eliminates a separate distant surgical site with potential for infection as well as an additional site of postoperative pain. Glenohumeral injuries associated with clavicle fractures have been reported to be as high as 46%, 18 and arthroscopy enables treatment of concomitant shoulder pathology at the same setting. This technique allows for a minimally invasive harvest-site incision, yet the arthroscopic assistance permits maximal visualization of the harvest site to ensure sufficient harvest of potential graft as well as avoiding iatrogenic injury to the rotator cuff and articular cartilage.…”
Section: Discussionmentioning
confidence: 99%